The effect of compression loading on fatigue crack propagation after a single tensile overload at negative stress ratios. (May 2018) - Bai, Shigang; Sha, Yu; Zhang, Jiazhen
Highlights: Compression loading in cycles can reduce the retardation caused by a tensile overload. A tensile overload in loading cycle produces an additional reverse plastic damage. The compression loading further increases the additional reverse plastic damage. The additional reverse plastic damage can balance the shielding effect of overload. Abstract: Experiments on fatigue crack propagation under a loading history with a single tensile overload at an overload ratio of R OL  = 1.8 were performed at different baseline stress ratios of R  = 0, −0.25, and −1 for aluminium alloy 2A12-O. The widely accepted fatigue crack propagation retardation due to a single tensile overload (OL) in the case of a positive stress ratio ( R ) was observed at R  = 0. However, the retardation effect gradually decreased from R  = 0 to R  = −0.25 and disappeared at R  = −1. These results indicate that the applied compressive load has a significant effect on the fatigue crack propagation after a single tensile overload for aluminium alloy 2A12-O. To reveal the mechanism of this effect of compression loading, a detailed elastic-plastic finite element (FE) analysis was performed. Based on the results of finite element analysis, a mechanism of additional reverse plastic damage caused by compression loading was proposed to explain the interaction of tensile overload and compressive load. The parameter of reverse plastic zone size was applied to characterize the additional reverse plastic damage. A parameter describing the effect of compression loading on fatigue crack propagation retardation due to a single tensile overload was developed. Using this parameter it was verified that the mechanism of additional reverse plastic damage is effective to explain the compression loading effect on the fatigue crack propagation retardation due to a single tensile overload.